PERAN HUKUM NASIONAL DAN INTERNASIONAL DALAM KONSERVASI PENYU SEBAGAI SATWA LIAR YANG DILINDUNGI DI INDONESIA - Selmen, Deri; Ashibly, Ashibly; Fitri, Sherly Nelsa (TANJUNGPURA LAW JOURNAL, 2025)
AbstractThe role of sea turtles in maintaining the balance of marine ecosystems is well-documented. Their function in controlling algae growth, maintaining coral reef health, and improving soil fertility through nutrient cycling is well-established. However, the decline of sea turtle populations in Indonesia is a matter of significant concern, with numbers having decreased by 95% due to illegal hunting, egg exploitation, climate change, and habitat destruction. This study aims to analyse the existing legal framework, both national and international, in protecting sea turtles as protected wildlife. The research method employed a normative approach through a comprehensive review of the relevant literature and meticulous legal analysis.The results obtained demonstrate that domestic legal frameworks, including Law No. 5 of 1990 and Government Regulation No. 7 of 1999, have established a solid legal foundation for the protection of sea turtles. At the international level, the role of CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora) as a global legal framework is of paramount importance in prohibiting international trade in endangered species. However, implementation in Indonesia still faces various challenges, including weak law enforcement, lack of public awareness, and lack of coordination between agencies.It is recognised that successful legal protection of sea turtles depends on synergies between national policies, customary laws and international commitments.Community-based approaches through local engagement, ecotourism programmes, and culture-based education have proven effective in increasing awareness and compliance with conservation efforts. Consequently, there is a necessity for integrative strategies and cross-sectoral support to ensure the continued protection of sea turtles and their marine ecosystems.  AbstrakPenyu memiliki peran penting dalam menjaga keseimbangan ekosistem laut, seperti mengontrol pertumbuhan alga, menjaga kesehatan terumbu karang, dan meningkatkan kesuburan tanah melalui siklus nutrisi. Namun, populasi penyu di Indonesia menurun drastis hingga 95% akibat perburuan ilegal, eksploitasi telur, perubahan iklim, dan kerusakan habitat. Penelitian ini  bertujuan untuk menganalisis kerangka hukum yang ada, baik nasional maupun internasional, dalam melindungi penyu sebagai satwa liar yang dilindungi. Metode penelitian menggunakan pendekatan normatif melalui studi pustaka dan analisis hukum. Hasil penelitian menunjukkan bahwa kerangka hukum domestik seperti Undang-Undang Nomor 5 Tahun 1990 dan Peraturan Pemerintah Nomor 7 Tahun 1999 telah memberikan dasar hukum untuk perlindungan penyu. Di tingkat internasional, peran cites sebagai kerangka hukum global sangat signifikan dalam melarang perdagangan internasional spesies terancam punah. Namun, implementasi di Indonesia masih menghadapi berbagai tantangan, termasuk lemahnya penegakan hukum, kurangnya kesadaran masyarakat, dan minimnya koordinasi antarinstansi. Diketahui bahwa keberhasilan perlindungan hukum terhadap penyu bergantung pada sinergi antara kebijakan nasional, hukum adat, dan komitmen internasional. Pendekatan berbasis masyarakat melalui pelibatan lokal, program ekowisata, serta pendidikan berbasis budaya terbukti efektif dalam meningkatkan kesadaran dan kepatuhan terhadap upaya konservasi. Oleh karena itu, diperlukan strategi integratif dan dukungan lintas sektor untuk memastikan keberlanjutan perlindungan penyu serta ekosistem lautnya.